1991
DOI: 10.1161/01.atv.11.2.234
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of three mutations of the low density lipoprotein receptor gene in Italian patients with familial hypercholesterolemia.

Abstract: 1 FH is a heterogeneous condition, since at least four classes of functional defects have been observed that disrupt the synthesis, intracellular transport, LDL binding capacity, and internalization of the LDL-receptor complex.2 During the past few years, the availability of cDNA and genomic clones 3 " 5 has made it possible to characterize the mutations of the LDL receptor (LDL-R) gene at the DNA level. A large array of From the Istituto di Patologia Generale (NX., M.G., R.G., R.T., S.C.), Universita di Moden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 36 publications
(20 reference statements)
1
19
0
Order By: Relevance
“…The large deletion at the 5' end of the gene that we have observed in FH 51 is superficially similar to that described recently in an Italian patient by Lelli et al 26 (identified as FH 44 or FH Bologna). However, the 5' 29 ), but the restriction fragment patterns obtained with FH 172 differ, and blotting with exon-specific probes confirmed that exon 15 is also deleted in this patient.…”
Section: Figure 4 Southern Blots Confirming Deletions and Rearrangemsupporting
confidence: 90%
“…The large deletion at the 5' end of the gene that we have observed in FH 51 is superficially similar to that described recently in an Italian patient by Lelli et al 26 (identified as FH 44 or FH Bologna). However, the 5' 29 ), but the restriction fragment patterns obtained with FH 172 differ, and blotting with exon-specific probes confirmed that exon 15 is also deleted in this patient.…”
Section: Figure 4 Southern Blots Confirming Deletions and Rearrangemsupporting
confidence: 90%
“…Explants were cultured in 25 cm 2 flasks in DMEM (Dulbecco's modification of Eagle's medium), 100 IU/ml of penicillin, and 50 g/ml of streptomycin, 2 mM glutamine, 15% fetal calf serum, and 95% air-5% CO 2 as previously reported (20).…”
Section: Patientsmentioning
confidence: 99%
“…The cDNA clone pHF␀A1 of human ␀-actin was used to normalize the RNA filters. Northern blots were performed as described previously (20).…”
Section: Northern Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…9 All DNA samples were digested by using 5 to 10 U/g of several restriction enzymes, separated by agarose gel electrophoresis, transferred to nylon membranes, and hybridized with various LDL-R cDNA probes. 10 Polymerase chain reaction (PCR) amplifications of the promoter region and exons 1 to 18 of the LDL-R gene were carried out by using the primers reported by Hobbs et al 2 in a total volume of 50 L containing 100 ng of genomic DNA, 10 mmol/L Tris-HCl, 50 mmol/L KCl, 1.5 mmol/L MgCl 2 , 100 mol of each of the 4 nucleotides, 10 pmol of each primer, and 2 U of Taq DNA polymerase. Single-strand conformation polymorphism analysis was performed by using a vertical gel unit; 5 L of PCR product was mixed with an equal amount of 95% formamide, 20 mmol/L EDTA, 0.1% bromophenol blue, and 0.1% xylene cyanole; denatured at 96°C for 5 minutes; snap-cooled in 4°C ice water; and then loaded onto an 8% polyacrylamide gel containing 5% glycerol.…”
Section: Analysis Of the Ldl-r Genementioning
confidence: 99%